Information and Communication Technologies and Labor Productivity: A Dynamic Slacks-Based Data Envelopment Analysis - Santos-Arteaga, Francisco J.; Di Caprio, Debora; Tavana, Madjid (Journal of the knowledge economy, 2024)
The current paper analyzes the efficiency displayed by 24 European Union (EU) countries when fostering labor productivity and the value added via ICT investments. In particular, a dynamic slacks-based measure data envelopment analysis (SBM-DEA) model is applied to analyze the evolution of efficiency through the period 2006–2013. The ranking resulting from the SBM-DEA framework is compared with the evolution of the Digital Economy and Society Index (DESI) scores obtained by these countries. The behavior of the efficiency variables describes a group of highly ranked DESI countries exhibiting a consistent decrease in efficiency. At the same time, several lowly ranked DESI countries display efficient trends throughout the series. The results illustrate how the reliance of EU policies on the social aspects derived from the market penetration of ICTs to measure technological development contrasts with the decreasing efficiency returns derived from an increase in ICTs investment. Thus, while catching up may occur in productivity terms, divergences in technological and social developments widen as investment in ICT infrastructures continues to differ across EU countries.